2016
DOI: 10.1177/2156587216650793
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Marjoram

Abstract: Origanum majorana L. commonly known as sweet marjoram has been used for variety of diseases in traditional and folklore medicines, including gastrointestinal, ocular, nasopharyngeal, respiratory, cardiac, rheumatologic, and neurological disorders. Essential oil containing monoterpene hydrocarbons and oxygenated monoterpenes as well as phenolic compounds are chemical constituents isolated and detected in O majorana Wide range of pharmacological activities including antioxidant, hepatoprotective, cardioprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 35 publications
1
53
0
1
Order By: Relevance
“… 28 In sweet marjoram, a plant that exhibits anticancer activity, it has been reported that the presence of rosmarinic acid is associated with antioxidant activity, and also ursolic acid is associated with anticholinesterase inhibition activity. 29 Epicatechin gallate was only found in isopropanol extracts, which in green tea has been associated with tumor viability reduction and apoptosis induction in human colon adenocarcinoma cells (HT29). 30 Another study reported the presence of rutin, kaempferol, myricetin, and quercetin in a phytochemical screening (HPLC, Fourier transform infrared mass spectrometry) for Indian fruits of Physalis peruviana 31 ; none of these were found in this current study.…”
Section: Resultsmentioning
confidence: 99%
“… 28 In sweet marjoram, a plant that exhibits anticancer activity, it has been reported that the presence of rosmarinic acid is associated with antioxidant activity, and also ursolic acid is associated with anticholinesterase inhibition activity. 29 Epicatechin gallate was only found in isopropanol extracts, which in green tea has been associated with tumor viability reduction and apoptosis induction in human colon adenocarcinoma cells (HT29). 30 Another study reported the presence of rutin, kaempferol, myricetin, and quercetin in a phytochemical screening (HPLC, Fourier transform infrared mass spectrometry) for Indian fruits of Physalis peruviana 31 ; none of these were found in this current study.…”
Section: Resultsmentioning
confidence: 99%
“…Origanum majorana L. (Lamiaceae), commonly known as marjoram, is a herb native to the Mediterranean region and cultivated in many countries of Asia, North Africa, and Europe [ 11 ]. Marjoram presents a strong and pleasant fragrance and is widely used as a spice.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of antibacterial quaternary ammonium compounds or dental materials based on such compounds have been explored [27][28][29][30], as well as polymeric or inorganic nanoscale agents [31]. As for other therapeutic areas [32][33][34][35], mining natural sources such as bee products or medicinal plants and ethnopharmacology data have also been looked upon as a potential way forward. A preliminary search of the published clinical trials carried out for caries prevention with herbal products suggested that there is relatively broad heterogeneity in design, quality, and herbal products evaluated clinically for this purpose.…”
Section: Introductionmentioning
confidence: 99%